STRATEGI PEMASARAN JAHE MERAH INSTAN DI KECAMATAN WONOAYU SIDOARJO - administrator, administrator; Cadura, Yohanes Wahyudi; Daryanto, Didik (Fakultas Pertanian Universitas Wijaya Putra, 2023)
In Lambangan Village, Wonoayu District, Sidoarjo Regency, there are severalMSMEs that produce instant red ginger, one of which is Hensam Sari Instant Red Ginger,El Nuha Red Ginger, Instant Red Ginger Mawaddah, which has been running since 2016and produces instant red ginger powder. and Temulawak. The drink's beautiful color andnot too spicy taste make red ginger syrup Aroma Hensam Sari Jahe Merah Instant, lovedby children to adults. This study has the objectives to 1). To find out the internal factorsand external factors which are the strengths and weaknesses as well as the opportunitiesand threats to MSMEs in Lambangan Village in marketing instant red ginger. 2) To findout the marketing strategy alternatives for instant red ginger that are implemented byMSMEs in Lambangan Village. 3). Want to know the marketing of instant red ginger thatis good for MSMEs in Lambangan Village. The research used the survey method, the datacollection method was carried out by interviews, observations and documentation studiesto the respondents, namely visitors and MSME managers in Lambangan Village directly.Methods of data analysis using quantitative description analysis. Analysis through QSPM.Strategic Decision Making Based on the SWOT analysis diagram, it is known that thealternative instant red ginger marketing strategy in Lambangan Village strongly supportsthe SO strategy, which consists of increasing production quantity, improving service toagents and customers.